Women's Experiences of Dyspareunia after Gynecological Cancer Treatment and Care-seeking Behavior: An Insight from a Qualitative Study. (1st August 2022) - Cyr, M; Dostie, R; Camden, C; Dumoulin, C; Bessette, P; Pina, A; Gotlieb, WH; Lapointe-Milot, K; Mayrand, M; Morin, M
ABSTRACT: Introduction: Dyspareunia frequently affects women after gynecological cancer treatment. The focus of previous studies has been on the biomedical factors contributing to dyspareunia in this population. To our knowledge, no study has yet examined the biopsychosocial factors associated with women's experiences of dyspareunia after gynecological cancer treatment. Moreover, cancer survivors appear to refrain from seeking care despite the consequences of dyspareunia. Objective: The aim of this study is to examine gynecological cancer survivors' experiences of dyspareunia and factors influencing their care-seeking behavior. Methods: A nested qualitative study was performed with the participants of a clinical trial investigating a multimodal pelvic floor physical therapy intervention. This enabled a comprehensive understanding of women's experiences and care-seeking behavior, including factors that could influence whether they seek care as well as their decision to undertake treatment. Women were included in the trial if they had completed endometrial or cervical cancer treatment and if they had experienced a minimum vulvovaginal pain intensity of 5 out of 10 during most intercourse attempts for at least 3 months. Individual semi-structured telephone interviews were conducted. The questions pertaining to women's experiences and factors influencing their care-seeking behavior were constructed based on the Common-Sense Model of Self-Regulation (i.e., identity, timeline, causes, consequences, and control attributes). The interviewer adopted a biopsychosocial perspective of health to approach these topics during the interviews. Interviews were recorded and transcribed for analysis using the interpretative description framework. Results: Of the 31 women included in the trial, 28 (90%) participated in the qualitative study. The participants had been diagnosed with different cancer stages and had received various treatments. For all participants, dyspareunia occurred after cancer treatment and persisted for a median time of 3 years (ranging from 3 months to 11 years). Loss of libido, lower vaginal lubrication, and reduced vaginal cavity were reported by women as contributing factors to dyspareunia. Participants explained how dyspareunia and these changes led them to engage in less, and even to interrupt, sexual activity. They also expressed that they were distressed, felt like less of a woman, and experienced low control and/or self-efficacy. Several women described that their condition had an impact on their relationship with their partner. Regarding factors influencing women's care-seeking behavior, participants emphasized that they were provided with insufficient information and support. Other barriers included balancing priorities, denial or reluctance, misbeliefs, resignation and acceptance, and negative emotions. Facilitators reported by women included acknowledgement of sexual dysfunction, desire for improvement, awareness of treatment possibilities, willingness to undertake treatment, and treatment acceptability. Conclusions: Women's experiences of dyspareunia after gynecological cancer treatment highlight the complexity of this condition, which involves biopsychosocial factors. The related consequences described by women also stress the importance of appropriate management. As the current study provides insight to guide the provision of services, efforts should focus on promoting the facilitators and overcoming the barriers to seeking care for sexual dysfunction after gynecological cancer treatment. Disclosure: No